Globalna przewaga konkurencyjna a strategia wiedzy - Stańczyk-Hugiet, Ewa (Global competitive advantage and knowledge strategy, 2005)
The paper is concerned with knowledge resources and possibilities of building global competitive advantage based on it. The first part presents the way global, multinational and transnational activities are perceived and characteristics. Then their different sources on competitive advantage are presented. Next potential knowledge strategie are identified in the context of competiors and the activity scope. Then there is a summary containing the results of the research into the sources of competitive advantage in enterprises located in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (3); 2005; nr 1093, s. 84-92